Spermatic feasibility after 20 years of freezing and refreezing: case study - Paulo Franco Taitson; Maria do Carmo Borges de Souza (Brazilian Archives of Biology and Technology, 2010)
The aim of the present work was to study the spermatic feasibility after 20 years of freezing, thawing and refreezing. A young man affected by testicular cancer sought the sperm freezing service. After 20 years, the samples were thawed and frozen again. After two days, thawing and analysis of the material took place. Comparison of the findings showed activity reduction from the first thawing to the fresh semen 59.09%. For the second thawing it was 77.27%. Considering the morphology, first thawing showed a reduction of 44.64% in relation to fresh semen. In the second thawing, the reduction was of 75%. Spermatic motility decreased by 64.28% in relation to fresh semen and 92.85% at the level of second thawing. The patient had gone through in vitro fertilization in 2007, obtaining success in the first one attempt. Este trabalho mostra a viabilidade espermática após 20 anos de congelamento seminal, descongelamento e novo congelamento. Jovem do sexo masculino afetado por câncer testicular procurou o serviço para congelamento de espermatozóides. Após vinte anos, as amostras foram descongeladas e congeladas novamente. Após dois dias, realizou-se um novo descongelamento e análise do material. As comparações dos resultados mostraram uma redução da atividade do primeiro descongelamento ao semen fresco em 59,09%. A partir do segundo descongelamento era de 77,27%. Considerando a morfologia, o primeiro descongelamento mostrou uma redução de 44,64% em relação ao sêmen fresco. No segundo descongelamento, a redução foi de 75%. A motilidade espermática diminuiu 64,28% em relação ao semen fresco e 92,85% a nível do segundo descongelamento. O paciente passou por fertilização in vitro em 2007, obtendo sucesso na primeira tentativa.